COMPARATIVE ASSESSMENT OF MORPHOLOGICAL AND MICROCIRCULATORY CHANGES IN THE THYMUS OF WHITE RATS IN ALIMENTARY ZINC (ZN) MICROELEMENTOSIS - Turdiev M. R.; Teshaev Sh. J. (Modern American Journals, 2025)
In this study, a comparative analysis of morphological and microcirculatory changes in the thymus of white rats with alimentary zinc (Zn) deficiency was conducted. During the experiment, dynamic changes in the lymphoid structures of the thymus, the degree of differentiation of thymocytes, the cortico-medullary ratio, and the reaction of stromal elements were morphometrically assessed. Disorders of parenchymal-stromal balance of the thymus, morphometric indicators of lymphoid tissue, a decrease in the number of lymphoid cells, as well as an increase in the thickness of the vessel wall and a decrease in the internal diameter of the organ were revealed. The obtained results highlight the important role of zinc in immunohomeostasis and create a scientific basis for a broader understanding of the immunopathological mechanisms of microelementoses.
Keywords: Zinc deficiency, thymus, white rat, T-lymphocytes, immune system.The actual ministry.